A facile route to prepare few-layer graphene/polyamide 6 nanocomposites by liquid reactive extrusion1. Issue 94 (14th October 2015) - Fu, Xubing; Zhao, Xingke; Yan, Dongguang; Zhao, Dajiang; Li, Jiao; Yang, Guisheng
<x xml:space="preserve">Abstract</x> A liquid reactive extrusion process was developed to prepare graphene/polyamide 6 nanocomposites and its crystalline and mechanical properties.